Enhancing the sustainability of rural water supply schemes in Emegua Kebele: the role of community participation and key challenges - Teklesinoda Asbetsadik; Arragaw Alemayehu; Dagim Wolde; Getabalew Derib (Discover Sustainability)
Abstract Assessing the sustainability of rural water schemes is vital for ensuring the well-being of communities and achieving sustainable development goals (SDGs). This study aimed to examine the sustainability of rural water supply schemes (RWSSs) in Emegua Kebele, focusing on the role of community participation in RWSSs. Data were collected through household surveys, key informant interviews, and focus group discussions. A two-stage sampling technique was used to select the Kebele, the water supply schemes, and the sample household of RWSS users. The sustainability status of RWSSs was assessed using nine indicators representing the economic, social, and environmental dimensions of the SDGs. The community participation index (CPI) was used to measure levels of community participation in RWSSs from the planning to evaluation phases using 15 activities. The study identified that while community involvement is essential, the current engagement and sustainability efforts are at a ‘moderate’ level. The study highlights the need for a more integrated approach to community participation in planning, implementation, and evaluation phases of RWSSs. The findings indicated, among others, the need for promoting effective community participation to better manage and maintain water supply systems and enhance their sustainability, and establishing clear communication channels between stakeholders, including local authorities and community members to foster a collective environment. The study found that insufficient users’ participation and inadequate technology selection are significant challenges that hinder the long-term viability of RWSSs. Based on the findings, the study provided recommendations for enhancing community engagement and ensuring sustainability of RWSSs, and for future research.